AKTIVITAS ANTIBAKTERI GETAH PEPAYA KERING TERHADAP Staphylococcus aureus PADA DANGKE [Antibacterial Activity of Dried Papaya Latex toward Staphylococcus aureus in Dangke] - Rifah Hestyani Arum; Budiatman Satiawihardja; Harsi D. Kusumaningrum (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2014)
AKTIVITAS ANTIBAKTERI GETAH PEPAYA KERING TERHADAP Staphylococcus aureus PADA DANGKE[Antibacterial Activity of Dried Papaya Latex toward Staphylococcus aureus in Dangke]Rifah Hestyani Arum1), Budiatman Satiawihardja1,2) dan Harsi D. Kusumaningrum1,2,3)*1)Program Studi Ilmu Pangan, Institut Pertanian Bogor, Bogor2)Departemen Ilmu dan Teknologi Pangan, Fakultas Teknologi Pertanian, Institut Pertanian Bogor, Bogor3)Southeast Asian Food and Agricultural Science and Technology (SEAFAST) Center, Bogor Diterima 19 November 2013 / Disetujui 12 Mei 2014ABSTRACT Dangke is a traditional milk curd product, made by coagulation of milk using fresh papaya latex. This product is usually kept at room temperature (27-30ºC) until consumption. Dried papaya latex was used in this study to produce dangke, and its effect to S. aureus was determined by direct contact in TSB and dangke. Fresh papaya latex was dried using vacuum oven at 50-55ºC for 22 hours. Dried papaya latex at a concentration of 2.7x10-3 g/100 mL could reduce S. aureus approximately 1 log CFU/mL in TSB after 24 hours. Dried papaya latex and papain could maintain the S. aureus number in dangke within 24 hours storage at room temperature. The antibacterial activity of non-proteolytic compound of papaya latex, i.e ethanolic extract of papaya latex was determined by macrodilution method, resulted an the MIC90 of 8 mg/mL. The cell membrane leakage after exposure was detected by measuring the optical density of bacterial supernatant at 260 nm. The result showed that exposure to increasing antibacterial concentration resulted in increasing of optical density of S. aureus supernatant, indicating that the antibacterial caused the S. aureus membrane leakage. Fluorescence microscopy imaging showed that S. aureus exposure to antibacterial caused membrane leakage thus gave Propidium Iodide (PI) chance to penetrate into the cell, as indicated by changing of fluorescence color from green to red.